Effect of different spacing on weed interference and performance of watermelon (Citrullus Lanatus) in South Western Nigeria Rainforest Zone - Adenubi OO; Sanni KO (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2020)
The spatial distribution of plants in a crop community is an important determinant of yields. An attempt was made to evaluate the effect of different spacing on weed interference, growth and yield of watermelon in Ikorodu agro-ecology during the rainy season of 2019. Three different spacing namely: 1m x 1m, 1m x 0.5m, and 1m x 1.5m replicated three times were used. Data collected included weed fresh weight, weed cover score, weed density, vine length, number of leaves, vine girth at 3, 6 and 9 weeks after planting (WAT) and number of fruit, fruit diameter and yield per plot at harvest. Data collected were subjected to one-way analysis of variance (ANOVA) and where significant difference exist, means of treatments were compared using Duncan Multiple Range Test (DMRT) at 5% level of probability. Results showed that sowing watermelon at 1m x 0.5m produced plants with thicker vines (4.10cm) and weed cover score (4.00) compared to sowing at 1m x 1m (3.86cm) and (6.66) respectively. Watermelon spaced at 1m x 1m spacing has the highest number of fruit (6.67) and fruit diameter (11.99cm) follow by 1m x 0.5m (4.67) and (10.79cm) and 1m x 1.5m having the least number of fruit and fruit diameter respectively. For optimum weed suppression which will in turn increase yield of the crop, it is therefore suggested that farmers should adopt 1m x 0.5m spacing in watermelon production. Further study in other humid agro ecological zone is equally recommended.